Studi Evaluasi Pelaksanaan Pembelajaran Ekonomi berbantuan E-learning di SMA Negeri 6 Denpasar - Sucitasari, L.K.; Sunu, I.G.K.A.; Sanjaya, D.B. (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aimed to determine the results of evaluations separately or together on context, input, process, product and problems that occur in the implementation of economic learning assisted by e-learning at SMA Negeri 6 Denpasar. This research is a program evaluation research using CIPP model. The sample of this study consisted of 85 students and 2 teachers of economics at SMA Negeri 6 Denpasar. Context, input, process, product data in this study were collected using a questionnaire using a Likert scale of 1-5. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of implementing the economic learning assisted by e-learning, the raw scores were transformed into Z-scores, then into T-scores, then verified into the Glickman Quadrant. Based on the research that has been done, the results show that: 1) The effectiveness of the implementation of economic learning assisted by e-learning in terms of the context obtained effective results (+), 2) The effectiveness of the implementation of economic learning assisted by e-learning in terms of the input obtained effective results (+), 3) The effectiveness of the implementation of economic learning assisted by e-learning in terms of the process obtained less effective results (-), 4) The effectiveness of the implementation of economic learning assisted by e-learning in terms of the product obtained effective results (+), 5) The results of a joint evaluation of the implementation of economic learning assisted by e-learning in terms of context, input, process, product obtained effective results (+ + - +), and 6) The problems faced in implementing e-learning assisted economic learning are 1) lack of support for facilities and infrastructure, 2) lack of student attendance, 3) many students submit assignments not on time, 4) students do not access the material provided, 5) lack of training regarding e-learning assisted learning, and 6) teachers lack time to explain the material.